Engenharia didática aplicada ao ensino de desenho técnico : uma sequência envolvendo gamificação - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Technical Drawing is a curricular component of most engineering higher education courses, in which the future engineer learns a graphic representation language that makes him capable of expressing his ideas and preparing his projects. However, there is a concern on the part of teachers in this area to motivate students to learn, leading them to seek new incentive techniques such as, for example, active teaching learning methodologies. Gamification was chosen as a strategy for this research, as relevant results in applications raised by bibliographic research. The study aims to use a didactic engineering as a research methodology and technique, to apply a didactic sequence involving gamification in three classes of the curricular component of Technical Drawing 2 at UNIPAMPA. This methodology is divided into four consecutive phases: it starts with the preliminary analysis, in which the conditions of the reality where the experience was applied were surveyed; followed by a priori design and analysis, in which they were identified as variables that influence the learning of Technical Drawing 2; in the application phase of the didactic sequence, two gamified activities were developed and applied, a game in Quiz format and a Bingo; in the a posteriori analysis and evaluation, the test results obtained from the students were compared and were selected as property of the research. It was found that didactic engineering changed the organization and application of research efficiently. Gamification met the need to motivate students, because during the activities they were engaged and participative. The study promoted an unprecedented action in the teaching of Technical Drawing 2, since, in general, teachers tend to adopt conventional teaching methods.
Keywords: Ensino de desenho técnico; Engenharia didática; Gamificação; Technical drawing teaching; Didactic engineering; Gamification; CNPQ::CIENCIAS SOCIAIS APLICADAS